Does market-oriented education systems improve performance or increase inequality: A configurational comparative method for understanding (un)intended educational outcomes - Ramsey Wise (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2015)
Since the introduction of PISA in 2000, school choice has been featured as a mechanism by which students gain equal educational opportunities and schools are pressured to improve their performance. In opposition, critics have argued that geographic and socioeconomic disparities may cause choice to unintentionally contribute to further educational inequalities, while performance gains are only marginal. To further explore the market rationale behind these claims, this study develops a conceptual framework that theoretically identifies complementary school-level characteristics of market-oriented education systems. These include choice, autonomy and accountability. Both educational outcomes - educational performance and inequality - are then analyzed with regard to these characteristics of market-oriented education systems using fuzzy-set qualitative comparative analysis (fsQCA). This configurational comparative approach further allows for the analysis of complex causality in order to understand how features of market orientation (i.e. choice, autonomy and accountability) also interact with a country's socio-structural context. Therefore, market orientation is modeled along with two well known contributing factors of the outcomes explored, namely social stratification and the institutional stratification of educational systems. Data is derived from the 2009 PISA study and aggregated for 21 OECD countries. The results demonstrate that a strong trade-off between performance and inequality is demonstrated in most countries sampled here. Although many of these countries indeed have market-oriented education systems, few cases contradict this association - the primary difference being the socio-structural context. Theoretically and empirically relevant configurations are identified to explain cross-national variation of educational outcomes; however, these solutions are highly sensitive and possibly subject to model ambiguities. – – Seit der ersten PISA Studie im Jahr 2000 wird "school choice" als Mittel angesehen, um Schülern gleiche Bildungschancen zu gewähren und die Leistungen von Schulen zu verbessern. Dagegen argumentieren Kritiker, dass die Schulwahl aufgrund geografischer und sozioökonomischer Disparitäten zu weiteren Bildungsungleichheiten beiträgt - während Leistungssteigerungen nur marginal sind. Um das hinter dieser Debatte stehende Marktprinzip zu untersuchen, liefert die vorliegende Studie einen konzeptionellen Rahmen, in dem theoretisch relevante, komplementäre Merkmale marktorientierter Bildungssysteme auf der Schulebene identifiziert werden. Hierbei handelt es sich um Wahl, Autonomie und Verantwortlichkeit. Beide Bildungsoutcomes - Ungleichheit und Leistung - werden in Bezug auf die genannten Merkmale marktorientierter Bildungssysteme unter Verwendung einer "fuzzy set Qualitative Comparative Analysis" (fsQCA) untersucht. Diese Methode ermöglicht die Analyse komplexer Kausalitäten, sodass zudem überprüft werden kann, inwiefern Wahl, Autonomie und Verantwortlichkeit mit dem sozialstrukturellen Kontext eines Landes interagieren. Auf diese Weise wird Marktorientierung zusammen mit zwei bekannten Einflussfaktoren für Ungleichheit und Leistung modelliert: soziale Stratifizierung und institutionelle Stratifizierung des Bildungssystems. Als Datenbasis dient die PISA-Studie 2009, auf deren Grundlage Daten für 21 OECD-Länder aggregiert wurden. Die Ergebnisse zeigen, dass ein Großteil der hier betrachteten Länder einen starken Trade-off zwischen Leistung und Ungleichheit zeigt. Dies betrifft vornehmlich marktorientierte Bildungssysteme. Allerdings, widerlegt eine kleine Anzahl von marktorientierten Ländern, die sich im Wesentlichen im sozialen Kontext unterscheiden diesen Zusammenhang. Theoretisch und empirisch relevante Merkmalskonfigurationen werden ermittelt, um länderübergreifende Veränderungen in den Bildungsoutcomes zu erklären. Die Ergebnisse sind allerdings anfällig für Modell-Ambiguität.
Keywords: 300